Techniques and Considerations for the Operative Treatment of Ankle Fractures in the Elderly. (2nd January 2019) - Konopitski, Andrew; Boniello, Anthony J.; Shah, Mitesh; Katsman, Anya; Cavanaugh, Garrett; Harding, Susan
Abstract : In managing fragility fractures about the ankle, nonoperative treatment should be considered with the caveat that soft-tissue integrity is of the utmost importance. Consultation with medical and nutritional services for the comanagement of elderly patients with a fragility ankle fracture improves outcomes. Soft-tissue preservation in the elderly is optimized with the judicious use of a tourniquet. In elderly patients, a congruent ankle joint with axial alignment and stability should be emphasized over achieving anatomic articular reduction. Less invasive surgical techniques, such as percutaneously placed anterior-to-posterior screws for posterior malleolar fractures and intramedullary fibular fixation, should be considered in the elderly. Construct stability in elderly patients is maximized with the use of lateral locking plates, tibia-pro-fibula screws, and bicortical medial malleolar screws. The use of external fixation with hydroxyapatite-coated pins should be considered in the treatment algorithm for fragility ankle fractures in elderly patients.